Rancang Bangun Sistem Informasi Pengendalian Penanganan Klaim Dengan Administrative Workflow Systems Pada PT. E-T-A Indonesia Berbasis Web - Sanada, Tommy; Tjandrarini, A.B.; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract : PT. E-T-A Indonesia is one of E-T-A German subsidiary that supply a circuit breaker for electro-mechanical and electro for a variety of industrial applications. At now, all departments that handle the claims should always check and open a files that integrated by Local Area Network (LAN) to determine the claims that will be done. Besides, the information from claims monitoring has not available yet. That problem can make the claims handling process has been delayed and can decrease the impact level on customer satisfaction. Based on that problems, this research will design and implement claims handling control information system to provide the monitoring claims information using administrative workflow systems methods that can help to control the timing of the claims handling process. This information system is build based on web. Web is used to provide the monitoring information claims to be accessible anywhere and anytime. The research result showed that handling control information systems can help PT. E-T-A Indonesia in controlling and monitoring the claims. Claims handling control information system is also able to help PT. E-T-A Indonesia to entry the claim data in an integrated way.